Lampung Culinary Information System - Ochi Marshella Febriani; Nursiyanto Nursiyanto; Ayu Firdhayanti; Deppi Linda (Proceeding International Conference on Information Technology and Business, 2022)
Many people in the city of Bandar Lampung have difficulty finding and getting information on culinary specialties of Lampung because there is no special promotion information system for typical Lampung culinary based on culinary categories and how is the process for booking culinary places in the Bandar Lampung City area. Based on these problems, the solution was to build a website-based Hits Culinary Information System to help the community, especially visitors from inside and outside the city of Bandar Lampung, in finding information about the culinary specialties of Lampung in the City of Bandar Lampung. The Hits Culinary Information System in the Bandar Lampung City area provides information and assists several culinary partners in developing their business such as product promotion and assisting visitors in the process of ordering food menus for reservations. The method used to develop the system is the waterfall method with a system developer tool, namely UML with several design stages, namely Use cases, Class Diagrams, Activity Diagrams, Sequential Diagrams. Then the system is built using the PHP programming language and MySQL database. The purpose of the research is to produce information media that can provide information on various kinds of Lampung culinary specialties as a form of introducing the typical food of the Lampung region. As well as expanding promotions from various partners throughout Bandar Lampung. The purpose of the research is to produce information media that can provide information on various kinds of Lampung culinary specialties as a form of introducing the typical food of the Lampung region. As well as expanding promotions from various partners throughout Bandar Lampung. The purpose of the research is to produce information media that can provide information on various kinds of Lampung culinary specialties as a form of introducing the typical food of the Lampung region. As well as expanding promotions from various partners throughout Bandar Lampung. Keywords—Information System, Culinary, Promotion and Ordering.